EBNA-1, a Bifunctional Transcriptional Activator - Kennedy, Gregory (American Society for Microbiology, 2003)
Transient-transfection assays have been used to identify transcription factors, and genetic analyses of these factors can allow a dissection of their mechanism of activation. Epstein-Barr nuclear antigen 1 (EBNA-1) has been shown to activate transcription from transfected templates, but its ability to activate transcription from nuclear templates has been controversial. We have established cells with integrated EBNA-1-responsive templates and have shown that EBNA-1 activates transcription from these chromatin-embedded templates dose dependently. A mutational analysis of EBNA-1 has identified a domain required for transcriptional activation of integrated templates, but not of transfected templates. The ability of EBNA-1 to activate transcription from both integrated and transfected templates can be inhibited by a derivative of EBNA-1 lacking the amino acids required for activation from integrated templates. EBNA-1's mode of activating transfected templates is therefore genetically distinct from that acting on integrated templates.